2014
DOI: 10.1517/17425255.2015.973401
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial toxicity of cardiac drugs and its relevance to mitochondrial disorders

Abstract: Most of the drugs used in cardiology are somewhat mitochondrion-toxic. The degree of toxicity, however, is variable and dependent on the type of drug, tissue, organ, subject, cell system investigated, the co-medication, and the conditions under which the investigations have been carried out. Abnormalities induced by mitochondrion-toxic cardiac drugs include impairment of respiratory chain functions resulting in reduced ATP production, increased production of reactive oxygen species with increased oxidation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Propranolol and atenolol at 5, 10 and 20 µg/ml increased ROS generation in the mitochondria obtained from the heart. These results are in agreement with previous studies which showed some beta-blockers can increase the generation of ROS in several tissues [7,8]. Thus, propranolol and atenolol may impair cardiac function through increase the generation of ROS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Propranolol and atenolol at 5, 10 and 20 µg/ml increased ROS generation in the mitochondria obtained from the heart. These results are in agreement with previous studies which showed some beta-blockers can increase the generation of ROS in several tissues [7,8]. Thus, propranolol and atenolol may impair cardiac function through increase the generation of ROS.…”
Section: Discussionsupporting
confidence: 93%
“…Propranolol (nonselective β receptor blocker) and atenolol (β 1 selective Beta-blockers) are among the beta-blocker drugs used in the treatment of many CVDs [4][5][6]. It has been shown that mitochondria are one of the targets of cardiac drugs, and also most of these drugs can cause mitochondrial toxicity [7]. Research has shown that some beta-blocker drugs are able to a generation of reactive oxygen species (ROS) [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukopenia, in addition to toxic neurological effects, is the primary toxic effect of DTX [ 47 ]. But, in human neutrophils, granulocytes, and lymphocytes, clopidogrel has been shown to decrease the membrane potential of the inner mitochondrial membrane, increase ROS production, and induce cytochrome-c release into the cytoplasm ultimately leading to apoptosis [ 55 ]. Therefore, leukocytes affected by anticancer drugs may be more susceptible to apoptotic process during combined treatment with clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…LD triggers apoptosis in several cellular models by impairment of respiratory chain functions resulting in reduced ATP production, depolarization of the mitochondria, loss of mitochondrial membrane potential ( ∆ Ψ), and overproduction of intracellular ROS [ 10 , 17 , 29 34 ]. The increased production of ROS correlates with decreased cell viability after exposure to LD, and ROS plays a vital role in inducing apoptosis of corneal cells and corneal endothelial dysfunction [ 34 37 ].…”
Section: Discussionmentioning
confidence: 99%